THE URGENCY OF PARENTAL INVOLVEMENT IN EARLY CHILDHOOD EDUCATION - Dianti Candra Septianti (Journal of Art and Creativity in Early Childhood Education, 2025)
This research examines the urgency of parental involvement in the administration of early childhood education (ECE). It was found that parental participation is very important to support student development, shape positive behavior, and enhance adaptation skills to globalization. Although the role of parents is often considered trivial, its impact on a child's character is very significant. Research shows that parental involvement can be realized through various activities with teachers, both at home and at school, to optimize children's development. However, there are issues in the relationship between parents and schools, where many parents tend to fully entrust the education process to teachers without understanding their child's abilities. This research emphasizes the importance of positive communication and collaboration between parents and schools to create a supportive learning environment. Through the literature review method, the author presents various research findings that show parental involvement contributes to children's academic success and character development. The conclusion of this research is that the role of parents in education is very multifaceted and crucial. Active involvement from parents can help create a comfortable and collaborative learning environment, as well as support the development of children's independence. Increased awareness and efforts from both parties are necessary to ensure the continuity of education between home and school. Further research is recommended to explore other factors influencing parental involvement in children's education.